Long-term Prospective Clinical and Magnetic Resonance Imaging–Based Evaluation of Matrix-Induced Autologous Chondrocyte Implantation. Issue 3 (March 2021) - Ebert, Jay R.; Fallon, Michael; Wood, David J.; Janes, Gregory C.
Background: Matrix-induced autologous chondrocyte implantation (MACI) has demonstrated encouraging midterm clinical outcomes, although published studies presenting longer-term clinical and radiological outcomes, across varied tibiofemoral and patellofemoral graft locations, are scarce. Purpose: To present the clinical and radiological outcomes a minimum of 10 years after surgery in a consecutive series of patients who underwent MACI in the tibiofemoral or patellofemoral knee joint. Secondly, to investigate any association between outcomes and patient characteristics, graft parameters, and injury and surgery history. Study Design: Case series; Level of evidence, 4. Methods: Overall, 87 patients (99 grafts: 57 medial femoral condyle, 24 lateral femoral condyle, 11 trochlea, 7 patella) were prospectively evaluated clinically and with magnetic resonance imaging (MRI) before surgery and at 2, 5, and minimum 10 years after MACI (mean, 13.1 years; range, 10.5-16 years). Patients were evaluated with a range of patient-reported outcome measures (PROMs), including the Knee injury and Osteoarthritis Outcome Score (KOOS) and patient satisfaction. The 6-minute walk test, active knee range of motion, and peak isokinetic knee extensor and flexor strength were assessed. Limb symmetry indices (LSIs) were calculated for strength measures. MRI was undertaken to evaluate the repair tissue, and an MRI composite score was calculated. Results: All PROMs significantly improved ( P < .05) over the pre- to postoperative period. Apart from KOOS Sport ( P = .018) and the LSI for peak isokinetic knee extensor strength ( P = .005), which significantly improved, no significant change ( P > .05) was observed from 2 years after surgery to final follow-up (range, 10.5-16 years) in all other PROMs, 6-minute walk distance, active knee range of motion, and the LSI for peak isokinetic knee flexor strength. At final follow-up, while the mean LSIs for peak isokinetic knee flexor and extensor strength were 96.9% and 95.7%, respectively, 74.7% of patients were satisfied with their ability to participate in sports, and 88.5% were satisfied overall. A nonsignificant decline was observed for tissue infill ( P = .211) and the MRI composite score ( P = .099) from 2 years to final review. At final MRI review, 9 grafts (9.1%) had failed. While no significant association ( P > .05) was observed between clinical or MRI-based outcomes and patient demographics (age, body weight, body mass index), defect size, or the duration of preoperative symptoms, the number of previous surgical procedures was significantly and negatively associated with KOOS Symptoms ( P = .015), KOOS Sport ( P = .011), and the degree of tissue infill ( P = .045). Conclusion: MACI provided high levels of satisfaction and adequate graft survivorship as visualized on MRI at 10.5 to 16 years after surgery.